Risk factors for high cerebral blood flow velocity and death in Kenyan children with Sickle Cell Anaemia: role of haemoglobin oxygen saturation and febrile illness. - Makani, J; Kirkham, F; Komba, A; Ajala-Agbo, T; Otieno, G; Fegan, G; Williams, T; Marsh, K; Newton, C (2009)
High cerebral blood flow velocity (CBFv) and low haemoglobin oxygen saturation (SpO(2)) predict neurological complications in sickle cell anaemia (SCA) but any association is unclear. In a cross-sectional study of 105 Kenyan children, mean CBFv was 120 +/- 34.9 cm/s; 3 had conditional CBFv (170-199 cm/s) but none had abnormal CBFv (>200 cm/s). After adjustment for age and haematocrit, CBFv > or =150 cm/s was predicted by SpO(2) < or = 95% and history of fever. Four years later, 10 children were lost to follow-up, none had suffered neurological events and 11/95 (12%) had died, predicted by history of fever but not low SpO(2). Natural history of SCA in Africa may be different from North America and Europe.